Menelaah Penerapam Total Quality Management pada Lembaga Perpustakaan - Putri, Kurnia; Sayekti, Retno; Faturrahman, Muslih (ARZUSIN, 2023)
This study discusses the Strategy for the Implementation of Total Quality Management (TQM) in the Regional Public Library of South Labuhanbatu Regency. This study aims to determine the TQM planning process at the Regional Public Library of South Labuhanbatu Regency, to determine the process of organizing TQM at the Regional Public Library of South Labuhanbatu Regency, to determine the process of implementing TQM at the Regional Public Library of South Labuhanbatu Regency and to determine the process of TQM supervision at the Public Library. South Labuhanbatu Regency. This type of research is descriptive with a qualitative approach. The techniques used in data collection are interviews, observation, and documentation. While the data analysis technique went through three stages, namely, data reduction, presentation and drawing conclusions. The results of this study indicate that the strategy of implementing Total Quality Management (TQM) at the Regional Public Library of South Labuhanbatu Regency has been going well, both in terms of planning, organizing, implementing, monitoring, and evaluating, but libraries should be able to apply more TQM to improve quality in library services.